Second Generation Drug-Eluting Stents for Endovascular Treatment of Ostial Vertebral Artery Stenosis: A Single Center Experience - Ortega-Gutierrez, Santiago; Lopez, Gloria V.; Edgell, Randall C.; Mendez, Aldo A.; Dandapat, Sudeepta; Roa, Jorge A.; Zevallos, Cynthia B.; Holcombe, Andrea L.; Hasan, David; Derdeyn, Colin P.; Rossen, James; Samaniego, Edgar A. (Frontiers in Neurology, 2019)
Objective: To report a single-center experience using drug-eluting balloon mounted stents (DES) for endovascular treatment of atherosclerotic ostial vertebral artery stenosis (OVAS). Background: Posterior circulation is affected in up to 25% of strokes, 20% of them resulting from atherosclerotic OVAS. The optimal management of symptomatic OVAS remains controversial. DES have been introduced to improve restenosis rates. Methods: We retrospectively analyzed prospectively collected data from patients with dominant OVAS who underwent endovascular treatment with second-generation DES placement. Patient demographics, clinical presentation, comorbidities, stenosis severity, stent features, technical success, complications and imaging follow-up were assessed. Results: Thirty patients were treated, predominantly male (86.6%). Sixteen patients presented with an acute stroke or TIA and fourteen were treated on an elective basis due to symptomatic chronic stenosis and contralateral occlusion. Comorbidities included hyperlipidemia (83%), hypertension (70%) and prior stroke (63.3%). Mean ostial stenosis at presentation was 80±14.8%. Twenty-one patients had contralateral VA involvement. DES deployment was technically successful in all patients using everolimus eluting stents in 30 lesions and zotarolimus eluting stents in two. One technical complication (stent migration) and three (10%) minor peri-procedural complications occurred. Complications included one asymptomatic ischemic infarct in the posterior circulation, one femoral artery thrombosis and one post-procedure altered mental status secondary to contrast induced neurotoxicity. Mean imaging follow-up was 8.8 months. Two (7.6%) patients had in-stent restenosis and underwent retreatment with angioplasty. There were no procedure-related mortalities. Conclusion: Our study confirms the feasibility of deploying DES for the treatment of ostial vertebral artery stenosis with low peri-procedural risk and low medium-term rates of re-stenosis.